ANALISIS KEBUTUHAN IMPLEMENTASI SEKOLAH PENGGERAK DALAM UPAYA MENUMBUHKAN PROFIL PELAJAR PANCASILA - Yuni, Yuni; Rejeki, Sri; Saddam, Saddam (Universitas Nahdlatul Ulama Blitar, 2026)
In the context of ongoing educational reform in Indonesia, this study aims to analyze the implementation requirements of the Sekolah Penggerak program in fostering the Pancasila Student Profile across three educational units in North Lombok Regency. Employing a qualitative research design, data were collected through in-depth interviews, direct observations, and document analysis. The study examines six key factors influencing program implementation: human resources, facilities and infrastructure, curriculum adaptation, extracurricular activities, school environment, and funding management. The findings reveal that successful implementation is strongly determined by the professional competence and leadership capacity of teachers and principals, the adequacy of school infrastructure, and the integration of Pancasila values into both curricular and co-curricular activities. Extracurricular programs play a significant role in shaping students’ character, while supportive school environments enhance internalization of core values. Furthermore, effective financial planning and allocation are essential to sustain program activities. This research contributes to the development of strategic frameworks for strengthening character education policy and improving the operational effectiveness of the Sekolah Penggerak initiative in Indonesia.